Stress and Non-Stress Roles of Inflammatory Signals during HSC Emergence and Maintenance - Clapes, Thomas; Lefkopoulos, Stylianos; Trompouki, Eirini (Frontiers in Immunology, 2016)
Hematopoietic stem cells (HSCs) are a rare population that gives rise to almost all cells of the hematopoietic system, including immune cells. Until recently, it was thought that immune cells sense inflammatory signaling and HSCs respond only secondarily to these signals. However, it was later shown that adult HSCs could directly sense and respond to inflammatory signals, resulting in a higher output of immune cells. Recent studies demonstrated that inflammatory signaling is also vital for HSC ontogeny. These signals are thought to arise in the absence of pathogens, are active during development and indispensable for HSC formation. In contrast, during times of stress and disease, inflammatory responses can be activated and can have devastating effects on HSCs. In this review, we summarize the current knowledge about inflammatory signaling in HSC development and maintenance, as well as the endogenous molecular cues that can trigger inflammatory pathway activation. Finally, we comment of the role of inflammatory signaling in hematopoietic diseases.